HAND HYGIENE COMPLIANCE STATUS OF MEDICAL STAFFS AT THE NATIONAL EYES HOSPITAL, IN 2021 (Vietnam Journal of Community Medicine, 2022)
Background: Hand hygiene (VST) is the simplest, most effective and most importantmeasure that contributes to reducing hospital-acquired infections, ensuring the safetyof health workers and improving the quality of patient care.Objectives: Describe the knowledge and practice of hand hygiene of medical staff atthe National Eye Hospital and analyze some related factors.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 323 health workers (NVYT),National Eye Hospital through questionnaires and observation using checklists. Theresearch results show that the knowledge and practice of hand hygiene in the controlof hospital-acquired infections of health workers is quite good.Conclusion: The rate of health workers with knowledge of hand hygiene reached74.9%. The rate of health workers with practices of hand hygiene reached over 85%.There are 4 factors related to knowledge of hand hygiene including: age, workingposition, working time and professional qualifications. Three factors related topractices of hand hygiene including: Gender, working position and time of trainingon infection control (p
Keywords: Hand hygiene, related factors, medical staffs.